Online Focus Group Discussions to Engage Stigmatized Populations in Qualitative Health Research: Lessons Learned - Gifty Marley; Rayner Kay Jin Tan; Tong Wang; Chunyan Li; Margaret E. Byrne; Dan Wu; Cheng Wang; Weiming Tang; Rohit Ramaswamy; Danyang Luo; Sean S. Sylvia; Joseph D. Tucker (International Journal of Qualitative Methods, 2023)
Community participation in research involving stigmatized populations has been sub-optimal, and digital tools could potentially increase participation in qualitative research. This study aims to describe the implementation of an online chat-based FGD (Focus Group Discussion) with men who have sex with men (MSM) in China as part of formative research for the PIONEER project, determine the advantages and limitations associated with the approach, and assess the feasibility of deepening community participation in STI research. Participants were involved in four days of asynchronous FGDs on sexually transmitted diseases and answered questions about the online FGD method. Online FGDs allowed us to deepen participant engagement through bidirectional communication channels. Data from online FGDs directly informed recruitment strategies and community participation for a clinical trial. Overall, 63% (29/46) of men who had never participated in offline LGBTQ + activities joined online FGDs. Many participants (89%, 41/46) noted that online FGDs were more convenient, less socially awkward, and more anonymous than in-person qualitative research. We highlighted potential risks as well as mitigation strategies when using online FGDs. Online FGDs were feasible among this group of sexual minorities and may be particularly useful in many cities where stigma limits in-person research participation.